2015
DOI: 10.1021/jp509800g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation on the Gas Phase Reaction of p-Cymene with Cl Atoms

Abstract: The rate coefficient for the gas-phase reaction of Cl atoms with p-cymene was determined as a function of temperature (288-350 K) and pressure (700-800 Torr) using the relative rate technique, with 1,3-butadiene and ethylene as reference compounds. Cl atoms were generated by UV photolysis of oxalyl chloride ((COCl)2) at 254 nm, and nitrogen was used as the diluent gas. The rate coefficient for the reaction of Cl atoms with p-cymene at 298 K was measured to be (2.58 ± 1.55) × 10(-10) cm(3) molecule(-1) s(-1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The uncertainties on the weighted average slopes are determined in accordance with the error propagation method, which is described below: where is the relative error on the average slope and and is the relative error on the individual slopes. The errors associated with the rate coefficients that incorporate the errors in the rate coefficients of the reference reactions are calculated by using the standard error propagation method following the equation …”
Section: Resultsmentioning
confidence: 99%
“…The uncertainties on the weighted average slopes are determined in accordance with the error propagation method, which is described below: where is the relative error on the average slope and and is the relative error on the individual slopes. The errors associated with the rate coefficients that incorporate the errors in the rate coefficients of the reference reactions are calculated by using the standard error propagation method following the equation …”
Section: Resultsmentioning
confidence: 99%
“…The quoted errors are two least-squares standard deviations and include uncertainties associated with the reported rate coefficients of the both reference reactions. Indicated errors are determined using the error propagation method, which we have discussed in detailed in our recent studies . Cuevas et al studied the rate coefficients of Cl atoms with ethyl acetate over the temperature range of 265–383 K using pulsed laser photolysis-resonance fluorescence technique (PLP-RF) at pressures between 20 and 200 Torr and they have found that there is no pressure dependence within the given uncertainty ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Rate coefficients for the reaction of 1,3-butadiene with Cl atom were measured over the temperature range 269–363 K using relative rate method. The complete experimental setup and the details were given in our earlier publications, and only a brief and necessary description is given here. All the experiments were performed in a double walled Pyrex chamber of volume 1250 cm 3 .…”
Section: Methodsmentioning
confidence: 99%